Patriotic Education of Teenagers throught theSpectrum of Movement «Atamanshchyna» in Ukrainian SSR in 1920–1924 - Krasnosiletskyi, Denys (Pedagogical Discourse, 2013)
This article examines the problems of the patriotic education among teenager throught of the antibolshevik movement of the uprising detachments in 1920 – 1924. Determination of concept «ataman» is offered, political directions of uprising motion and activity of insurgent detachments are reflected, displays are discussed by the insurgents of love for Motherland, self-sacrifices in a fight for independence of Ukraine. Attention is accented on the necessity of the use of this historical material teachers, as to the symbol of patriotism. It is extremely necessary for a rising generation on a way to forming of the all-round developed person in modern terms.